Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.